2000
DOI: 10.1590/s0004-28032000000100008
|View full text |Cite
|
Sign up to set email alerts
|

Hipocontratilidade do esôfago em pacientes com doença de chagas e pacientes com acalásia idiopática

Abstract: RESUMO -Em pacientes com esofagopatia chagásica e pacientes com acalásia, a amplitude das contrações esofágicas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
0
1
1
Order By: Relevance
“…The incidence of this disorder is variable among South American countries; it is responsible for up to 90% of achalasia cases in Brazil, 4,5 causes between 18% and 23% of the cases in Argentina, 6,7 and 13% of cases in Chile 8 . Several Brazilian reports indicate that idiopathic achalasia and achalasia related to Chagas disease differ 9,10 . Although we did not observe such differences a recently published report from Argentina found that patients with Chagas disease have acetylcholine M2 receptor circulating antibodies, 11–14 which could be involved in the pathophysiological mechanisms of the disease 15 …”
Section: Introductioncontrasting
confidence: 62%
“…The incidence of this disorder is variable among South American countries; it is responsible for up to 90% of achalasia cases in Brazil, 4,5 causes between 18% and 23% of the cases in Argentina, 6,7 and 13% of cases in Chile 8 . Several Brazilian reports indicate that idiopathic achalasia and achalasia related to Chagas disease differ 9,10 . Although we did not observe such differences a recently published report from Argentina found that patients with Chagas disease have acetylcholine M2 receptor circulating antibodies, 11–14 which could be involved in the pathophysiological mechanisms of the disease 15 …”
Section: Introductioncontrasting
confidence: 62%
“…Não foram encontradas diferenças entre pacientes com acalásia idiopática e aqueles com doença de Chagas na amplitude das contrações esofágicas (1,15) , destacando-se que nas duas doenças ela está diminuída em relação a pessoas normais (15) , e na amplitude das contrações em faringe, neste local sem diferença com pessoas normais (2) . A proporção de pacientes com contrações de baixa amplitude (inferior a 37 mm Hg) é maior nos pacientes com doença de Chagas do que naqueles com acalásia idiopática (13) . Trabalhos sobre a complacência esofágica também encontraram resultados semelhantes nas duas doenças, ou seja, aumento da complacência (19,24) .…”
Section: Doença De Chagas Acalásia Idiopáticaunclassified